Meltdown!: Local heating by decaying excited host positive polarons triggers aggregation quenching in blue PhOLEDs - Setzer, Tobias; Friederich, Pascal; Meded, Velimir; Wenzel, Wolfgang; Lennartz, Christian; Dreuw, Andreas (ChemPhysChem, 2018)
Exciton-polaron induced aggregation (EPIA) in organic host materials for blue Phosphorescent Organic Light Emitting Diodes (PhOLEDs) is driven by a non-radiative decay of electronically excited positive polarons resulting in a local heating of the amourphous host matrix. The released heat triggers morphological changes, i. e. molecular aggregation between neighboring host molecules. The resulting aggregates, which our calculations identify as carbazolyl dimers, lead to decreased PhOLED efficiency. Statistical assessment of some host-only morphologies reveals a structure-dependent propensity for molecular aggregation corroborating the identified EPIA mechanism. Our findings provide a fresh look at established molecular design rules and will help to improve blue PhOLED host materials to enhance blue PhOLED device lifetimes.
Gesehen am 30.09.2019